Considerations of Cloud Computing Contracts at the Conclusion Stage - Mohammadali Hasanian; Esmaeil Shahsavandi; Amirabbas Bozorgmehr (حقوق فناوریهای نوین)
Information technology is the avanguard technology of the modern age that has affected various aspects of life and improved the quality of human life. Cloud computing is the ability to provide information technology resources through the Internet, which offers a new approach compared to traditional approaches in looking at the physical infrastructure of data and applications. Based on the services that can be provided to customers, cloud computing includes three main service models: infrastructure as a service, platform as a service, and software as a service. As a result, cloud computing is a model for providing services in information technology, which allows storing and processing information in It provides internet platform or private networks. The contracts that are concluded between providers and users of cloud computing services are mainly standard or supplementary contracts. Legal relations in the field of cloud computing are regulated by contracts known as service level agreements and data related laws. Technically and legally, these contracts must be completely carefully prepared. To pay attention to both aspects are necessary and mandatory. The cloud computing contract, like other contracts, is subject to the general rules of contracts in terms of the conditions of conclusion; Like all contracts, both parties must have a serious and healthy will, their law should be recognized for the transaction, the purpose of the contract should be legitimate and its subject should be clear and certain. 1. Background and Purpose Information technology, one of the most advanced scientific and technical fields in the modern era, has influenced various aspects of human life and created new areas for information management and processing. Cloud computing, as one of the fundamental developments in this field, by providing the possibility of data storage and processing through the Internet, has created a fundamental transformation in the structure of information infrastructures. Due to the distributed and multi-layered nature of this technology, the conclusion of contracts related to the provision of cloud services has special features that distinguish it from traditional contracts. Since cloud computing contracts are usually drawn up as standard and adhesion contracts, numerous legal issues arise regarding the drafting of these contracts and the determination of the obligations and responsibilities of the parties. On the other hand, protecting user data, determining regulatory frameworks, how to enforce the obligations of cloud service providers, and freedom of will in standard contracts are among the important challenges in this field. The purpose of this research is to investigate the characteristics of cloud computing contracts, the legal requirements for concluding these contracts, the principles governing their drafting, and the impact of freedom of will in determining contractual terms. Also, this study seeks to examine the challenges related to the implementation of these contracts in different legal systems and provide a comparative analysis of international approaches in this area.